PASTORAL "BLUSUKAN" AS A MANIFESTATION OF INCARNATION THEOLOGY: IN THE CONTEXT OF PURWOKERTO DIOCESE - Setyawan, Antonius Ary (LOGOS, 2017)
The term incarnation is used to illustrate how God humbled Godself byÂ tranforming Himself into a human being like the believers so they canÂ comprehend the Kingdom of God. As Cristians, we are invited toÂ actualize the Kingdom of God in our everyday life. We are called also toÂ promote the Kingdom of God to all creatures especially those who areÂ poor, hungry, and suffering. â€œBlusukanâ€1 as an activity conducted by aÂ priest to go around and come in to the place that is rarely visited or notÂ most people preferred to come is a way to realize the theology ofÂ incarnation. With this way, a priest as a shepherd meet the people andÂ get to know them in their real situation. As Jesus - Son of God - whoÂ came among the people to save them in the incarnation, the presence ofÂ the priests through â€œblusukanâ€ pastoral strategy become the spiritualityÂ of diocesan priest that was expected to answer the needs of the people soÂ that they also experienced the salvation.